Análise teórica e experimental da utilização de gerador de indução trifásico na configuração fukami para excitação rotativa de geradores síncronos. - Metello, Elzio (2024)
The thesis presents the study of a non-conventional topology of a rotating exciter for synchronous generators. With the aim of highlighting the advantages of this topology compared to the PMG (Permanent Magnetic Generator) exciter used in diesel generator sets, this work proposes the application of a self-excited three-phase induction generator (SEIG) with a squirrel cage rotor, operating as a single-phase induction generator connected in the Fukami configuration (SEIG-Fukami) as a rotating exciter. For this study, a three-phase induction machine with 6 poles and 0.37 kW is used, coupled to the same shaft as a generation system composed of a three-phase synchronous machine of 3 kVA and 4 salient poles, along with a 2 kW direct current machine. The induction machine utilizes the Fukami configuration to generate a single-phase voltage, which is rectified to feed the field of the synchronous generator. This generated voltage is controlled by a PI control system to maintain a constant voltage level, and a speed control system is also employed to ensure a constant generation frequency. Thus, the proposed exciter showed good performance within the established values, in addition to addressing environmental aspects related to substitution and economic possibilities. Therefore, the performance of this exciter, along with the voltage control system, will be tested with the synchronous generator subjected to dynamic load. In this context, the validation of the thesis proposal is carried out by comparing experimental and computational results of the performance of this generation system.